Development and investigation of microwave radiation sources and detector sections using SBDs within the 220–400 GHz frequency range - Zorenko, A.V.; Kudryk, Ya.Ya.; Marunenko, Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
A procedure of mm- and submm-wave devices simulation based on the up-todate simulation techniques for bulk microwave structures is proposed. We demonstrate a possibility of making microwave radiation sources based on IMPATT diodes and frequency multipliers with frequency output of 280 GHz as well as detector sections with Schottky barrier diodes for the 220–325 GHz and 325–400 GHz frequency ranges.